1971
DOI: 10.1164/arrd.1971.104.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Mucous Gland Size in the Major Bronchi of Patients with Chronic Bronchitis, Asthma, and Asthmatic Bronchitis1–3

Abstract: __________________________________________________ ___Mucous gland size and the amount of muscle in the bronchi were measured in 7 patients with typical chronic bronchitis, 4 patients with chronic bronchitis and attacks of wheezing (chronic asthmatic bronchitis), and 3 patients with classic spasmodic asthma. The patients with asthma had increased bronchial muscle, but the patients with chronic bronchitis did not. Three of the 4 patients with asthmatic bronchitis had increased muscle; such patients can therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(44 citation statements)
references
References 10 publications
5
39
0
Order By: Relevance
“…MATSUBA and THURLBECK [7] found that the percentage of the airway wall area occupied by smooth muscle in central and peripheral airways was 2.6 and 14 in adults and 2.8 and 10 in children, respectively. These values for central airways are similar to those found in other studies: HALE et al [11] 2.5%, DUNNILL et al [12] 4.5% (range 2±11%), and TAKIZAWA and THURLBECK [6] 2.5%. SOBONYA [13] found a similar trend in relation to airway size even when comparing lobar with segmental airways.…”
Section: Distribution Within Bronchial Treesupporting
confidence: 91%
See 1 more Smart Citation
“…MATSUBA and THURLBECK [7] found that the percentage of the airway wall area occupied by smooth muscle in central and peripheral airways was 2.6 and 14 in adults and 2.8 and 10 in children, respectively. These values for central airways are similar to those found in other studies: HALE et al [11] 2.5%, DUNNILL et al [12] 4.5% (range 2±11%), and TAKIZAWA and THURLBECK [6] 2.5%. SOBONYA [13] found a similar trend in relation to airway size even when comparing lobar with segmental airways.…”
Section: Distribution Within Bronchial Treesupporting
confidence: 91%
“…TAKIZAWA and THURLBECK [6] examined sections from six matched central airways obtained at autopsy from each of three cases of fatal asthma, four cases of chronic bronchitis with episodes of wheezing during life ("asthmatic bronchitis") and seven cases of chronic bronchitis without wheezing. They found significantly more (~70%) smooth muscle in the airway wall in cases of asthma compared with cases of chronic bronchitis, with cases of asthmatic bronchitis falling between these two groups.…”
Section: Asthmamentioning
confidence: 99%
“…Numerous studies have noted increased airway smooth muscle mass in fatal asthma (1)(2)(3)(4)(5)(6)(7)(8)(9). Because of the obstacle of obtaining bronchial biopsies that include the full thickness of airway smooth muscle, fewer studies on airway smooth muscle mass in patients with nonfatal asthma exist.…”
Section: Increased Airway Smooth Muscle Mass In Asthmamentioning
confidence: 99%
“…Bronchial smooth muscle hyperplasia/hypertrophy is a wellrecognized pathological change in asthma (1)(2)(3). The volume of smooth muscle positively correlates with the magnitude of contraction, measured isometrically, induced by histamine, and carbachol (4).…”
Section: Introductionmentioning
confidence: 99%